Explaining the dramatic changes in performance of US banks: technological change, deregulation, and dynamic changes in competition - Berger, Allen N.; Mester, Loretta J. (Journal of Financial Intermediation, 2003)
We investigate the effects of technological change, deregulation, and dynamic changes in competition on the performance of US banks. Our most striking result is that during 1991–1997, cost productivity worsened while profit productivity improved substantially, particularly for banks engaging in mergers. The data are consistent with the hypothesis that banks tried to maximize profits by raising revenues as well as reducing costs. Banks appeared to provide additional or higher quality services that raised costs but also raised revenues by more than the cost increases. The results suggest that methods that exclude revenues when assessing performance may be misleading.